2022
DOI: 10.18231/j.ctppc.2022.026
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacological review of vinca plant for anticancer activity

Abstract: The strive of this assessment shows that Vinca rosea, many obviously grown vegetation round us which can be used for medicinal purposes. It has many known names like vinca Rosea, Madagascar periwinkle, vibrant eyes, Cape periwinkle, graveyard plant, old maid, crimson periwinkle, rose periwinkle myrtle. Ayurveda is the Indian conventional device of medication which focuses on the scientific capability of plant life. Catharanthus roseus is one plant recognized nicely in Ayurveda. It is known for its antitumour, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Studies have shown that flavonoids such as genistein, epigallocatechin, and resveratrol can stop the progression and prevent future metastasis of breast cancer (8). Currently, several chemotherapeutic drugs are isolated from natural products, such as vinblastine and vincristine derived from the plant Catharanthus roseus (9).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that flavonoids such as genistein, epigallocatechin, and resveratrol can stop the progression and prevent future metastasis of breast cancer (8). Currently, several chemotherapeutic drugs are isolated from natural products, such as vinblastine and vincristine derived from the plant Catharanthus roseus (9).…”
Section: Introductionmentioning
confidence: 99%